Tracking diversity and evolutionary pathways of Lebanese oak taxa through plastome analyses. Issue 3 (2nd July 2020) - Douaihy, Bouchra; Saliba, Carole; Stephan, Jean; Simeone, Marco Cosimo; Cardoni, Simone; Farhat, Perla; Bou Dagher Kharrat, Magda
ABSTRACT: The aim of this study is to better understand the phylogeography and evolution of the Lebanese oaks and to assess the convergence between their morpho-ecological and molecular characteristics. We investigated DNA sequence variation in four plastid markers ( TrnH-psbA, ycf1, trnK- matK and PetD ) of the seven species (three sections) occurring in Lebanon: Q. calliprinos, Q. infectoria, Q. kotschyana, Q. cedrorum, Q. cerris, Q. look, and Q. ithaburensis, in addition to Q. libani and Q. cerris from Syria, and possible hybrids. Among the four markers, the TrnH-psbA and trnK-matK loci resulted in the best-resolved genealogies. Quercus calliprinos haplotypes clearly belong to the west Asian-eastern Mediterranean 'WAHEA' lineage. Sect. Cerris haplotypes are derived variants of the central Mediterranean 'Cerris-Ilex' lineage. Sect. Quercus haplotypes were less differentiated and in close connection with the Caucasian primary refugium of white oaks. Despite the low species-level resolution, a gradient in genetic diversity linked to the ecological plasticity of the sampled species was observed. A close relationship of Q. look with Q. cerris is confirmed. Quercus kotschyana seems an ancient stock of closely related and disjunct oak of sect. Quercus . Finally, our results confirm the relevance of the Levant region as an important biogeographical crossroad between continents, and its key role in stimulating diversification and preservation of ancient genepools. Important areas in Lebanon that should be taken into consideration in future conservation strategies are highlighted, to ensure a wider genetic potential of local oak species to face the current climate change.